A multifunctional polyimide nanofiber separator with a self-closing polyamide–polyvinyl alcohol top layer with a Turing structure for high-performance lithium–sulfur batteries. Issue 9 (20th November 2020) - Luo, Xiang; Lu, Xianbo; Chen, Ya; Chen, Xiaodong; Guo, Hele; Song, Chunyu; Wang, Nannan; Su, Dawei; Wang, Guoxiu; Cui, Lifeng; Liu, Yan
Abstract : The development of commercial lithium–sulfur (Li–S) batteries is typically restricted by the intrinsic drawbacks of the dissolutiion and shuttling of lithium polysulfides (LPS) and the uncontrollable growth of lithium dendrites. Abstract : The development of commercial lithium–sulfur (Li–S) batteries is typically restricted by the intrinsic drawbacks of the dissolutiion and shuttling of lithium polysulfides (LPS) and the uncontrollable growth of lithium dendrites. To address these non-ignorable challenges, a multifunctional composite nanofiber-based separator consisting of an electrospinning polyimide (PI) substrate and a polyamide–polyvinyl alcohol (PA–PVA) top layer is designed and fabricated via interfacial polymerization (IP). In this situation, its superior features, such as desirable wettability, suitable porosity, excellent electrolyte uptake and retention, and high thermal tolerance, can be obtained. Besides, the architecture of the highly negatively charged PA–PVA top layer with a dense Turing structure can not only provide an electronegative environment to accelerate the Li + transmembrane transfer as well as simultaneously repel the negatively charged polysulfide ions, but also enable ordered Li + migration for homogeneous Li deposition on the anode. Due to these advanced structural characteristics, the Li–S battery assembled with the PI/PA–PVA separator gives a high initial specific capacity of 1499 mA h g −1 at 0.1C and a stable discharge capacity of 852 mA h g −1 with an ultralow fading rate of 0.1% per cycle after 500 cycles at 0.2C. More importantly, this PI/PA–PVA top layer has the functional characteristics of melting and self-closing at high temperatures, endowing the Li–S battery with excellent safety performance.